Policing global regions: the legal context of transnational law enforcement cooperation - Hufnagel, Saskia (Transnational criminal justice, 2021)
Police cooperation in legal and political diversity -- Policing in the Context of Global, Regional and Transnational Normmaking : Theories and Practice -- Legal Regulation of Global Policing : A tight patchwork? -- European Union Police Cooperation : Normmaking between peers? -- Cooperative Policing in Australasia : Two Big Fish in a Small Pond -- Law Enforcement Cooperation in Greater China : One Country, Four Systems? -- Law Enforcement in North America : Policing Across Three Distinct Systems -- Globalising Cross-Border Law Enforcement Regulation.